Effect of glass ball insertion on vortex-flow microfiltration of oil-in-water emulsion - Kim, JP; Kim, JJ; Min, BR; Chung, KY; Ryu, JH (ELSEVIER, 2002)
A new vortex-flow membrane module with glass balls was developed to enhance the permeate flux through a flat-sheet membrane. As a preliminary study for a practical application of our new module configuration, the effects of operating parameters on the microfiltration of an oil-in-water emulsion were investigated. The glass balls used in this study had an average diameter of 4 mm and an average weight of 0.08 g, giving an average density of 2.39 g/cm(3). The number of glass balls inserted into the module was 500, leading to an effective volume fraction of 0.23. Under the same operating conditions, a significant flux enhancement was observed in the presence of glass balls. The flux enhancement due to the presence of glass balls increased with the feed flow rate. The influence of glass balls on the flux enhancement was found to be most significant when the emulsion was more highly concentrated, indicating that the mechanism of this enhancement is based on the disruption of the concentration boundary layer.
Keywords: PROTEIN FRACTIONATION; FOULING CONTROL; WASTE-WATER; ULTRAFILTRATION; MEMBRANE; PERFORMANCE; PULSATION; YEAST